2019
DOI: 10.21203/rs.2.4294/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Results of Intraductal Meibomian Gland Probing Combined with Intense Pulsed Light in Treating Patients with Refractory Obstructive Meibomian Gland Dysfunction: A Randomized Controlled Trial

Abstract: Background: This study aims to optimize the therapeutic regimen for refractory obstructive meibomian gland dysfunction (o-MGD) patients by combining intraductal meibomian gland probing (MGP) and intense pulsed light (IPL) to enhance their positive effects and reduce their limitations. Methods: This randomized, assessor blind study includes 45 patients (90 eyes) with refractory o-MGD who were divided into 3 groups via allocation concealment: IPL (group I, received an IPL treatment course: 3 times at 3-week inte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 6 publications
0
34
0
Order By: Relevance
“…There are some differences between both devices such as the treatment schedule. The E [ Eye system is usually applied in three or four sessions, performed on days 1, 15, 45, and 75 [63,70,71], while the M22 system is usually applied in three sessions, separated by 3 or 4 weeks [62,71,72]. The spot size is 15 9 40 mm in E [ Eye and 15 9 35 mm in the M22, and the cooling system is Airflow in the E [ Eye and ChillTip TM Contact in the M22.…”
Section: Light-based Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some differences between both devices such as the treatment schedule. The E [ Eye system is usually applied in three or four sessions, performed on days 1, 15, 45, and 75 [63,70,71], while the M22 system is usually applied in three sessions, separated by 3 or 4 weeks [62,71,72]. The spot size is 15 9 40 mm in E [ Eye and 15 9 35 mm in the M22, and the cooling system is Airflow in the E [ Eye and ChillTip TM Contact in the M22.…”
Section: Light-based Devicesmentioning
confidence: 99%
“…Piyacomn et al [70] (I) observed a higher and faster improvement in the MG function in patients who combined conventional eyelid hygiene and IPL than in those patients who performed hygiene alone. Huang et al [72] (I) compared IPL with intraductal MG probing. They reported that the combination of both methods was more effective than separately in improving symptoms, BUT, meibum grade, and telangiectasias.…”
Section: Light-based Devicesmentioning
confidence: 99%
“…Four out of the 14 reviewed papers were published in 2019 alone. 13,14,23,30 Additionally, one review article looking at MGP was published this same year. 24 MGP is also mentioned in recent reviews looking at the treatment of MGD, with one published as recently as January, 2020.…”
Section: 1mentioning
confidence: 99%
“…22,23,25,26,36 Four of these five were conducted by the same first author using his past patients' charts. 22,23,25,26 Nine of the included articles described prospective studies, 10,13,14,16,21,29,30,34,38 four of which were RCTs. 13,14,16,21 A majority of the included studies had no control group.…”
Section: 1mentioning
confidence: 99%
“…5The CFS scores of each quadrant ranged from 0 to 3 (0: no punctate staining; 1: less than half was stained; 2: more than half was stained; and 3: the whole quadrant was stained). The total score was the sum of the four quadrants of the cornea [20].…”
Section: Clinical Examinations and Evaluationsmentioning
confidence: 99%